2019
DOI: 10.3390/ijerph16214142
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Analysis of Newly Built Houses

Abstract: Recently, people have become increasingly aware of potential health issues related to indoor environments. In this study, we measure the concentrations of various volatile organic compounds, carbonyl compounds, and semi-volatile organic compounds, as well as the ventilation rates, in 49 new houses with light-gauge steel structures one week after completion. The proper indoor air quality of new residential environments can be ensured by characterizing people’s exposure to certain chemicals and assessing future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This has resulted in an increased likelihood of chemical compounds being retained indoors and, in turn, increased air contamination. Various chemical compounds are emitted into indoor spaces by a wide range of sources, including building and indoor materials, furniture, curtains, air fresheners, deodorants, pesticides, personal care products, cooking, and other everyday household products [10,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has resulted in an increased likelihood of chemical compounds being retained indoors and, in turn, increased air contamination. Various chemical compounds are emitted into indoor spaces by a wide range of sources, including building and indoor materials, furniture, curtains, air fresheners, deodorants, pesticides, personal care products, cooking, and other everyday household products [10,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…For atopic dermatitis, relocation to or repair of a new house increased both diagnostic and therapeutic prevalence. This could have been caused by building materials and adhesives, which are sources of volatile organic compound emissions, particularly in newly built houses [18,21]. However, a history of atopic dermatitis in siblings and more time spent at school significantly decreased the risk of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been reported that almost no guidance or explanation from the construction company is received on SBS prevention [70]. This survey also found that the contractor was unaware of the improvement plan or the degree of effectiveness (Table 12).…”
Section: Awareness Of the Improvement From The Developermentioning
confidence: 84%
“…This distinction is important in the context of the standards used to benchmark the safety and acceptability of IAQ in educational buildings. Numerous longitudinal studies have shown that TVOC concentrations display a strong temporal dependency following the completion of new and renovated buildings (Holøs et al, 2019;Persson et al, 2019;Suzuki et al, 2019). Mysen et al (2003) and Wachenfeldt et al (2007) proposed that for buildings such as schools and offices indoor air pollution could be successfully controlled using demand-controlled mechanical ventilation.…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%